HIGH-TOOL - a strategic assessment tool for evaluating EU transport policies - Eckhard Szimba; Jan Ihrig; M. Kraft; Kay Mitusch; M. Chen; M. Chahim; J. van Meijeren; J. Kiel; Benedikt N. Mandel; A. Ulied; E. Larrea; G. De Ceuster; et al. (Journal of Shipping and Trade (JST), 2018)
In this paper the strategic transport policy assessment instrument HIGH-TOOL is presented. The model has been developed for the European Commission, allowing policy-makers to identify the most advantageous transport policies and to strategically evaluate the impacts of transport policies on transport, environment and economy. The main innovation of this policy assessment tool lies in the integration of originally independently functioning models - i.e. passenger and freight demand, demography, and vehicle stock models, as well as economic, environmental and safety assessment models. With its traffic zones at the regional level of NUTS-2 and its aggregated view on the transport system, the instrument has a relatively lean structure avoiding runtime problems, without losing the spatial dimension. What distinguishes HIGH-TOOL from all other European transport policy assessment instruments: the model is an open source tool, it is freely available and does not require any commercial software to be run. In combination with its modular structure the HIGH-TOOL model can relatively easily be adjusted to other modelling methodologies or data. It can also comparatively easily be made responsive to 'new' policies which are not in the scope of the current model version. Thus the HIGH-TOOL model lays the foundation for further innovations in the assessment of transport policies and mobility concepts.
Keywords: 650; Assessment tool; Transport policy; Transport demand modelling; Transport model; Impact assessment; European Union